ICT Disparities In Finland - Access and Implications - Näsi, Matti (fi=Turun yliopisto|en=University of Turku|, 2013)
The Internet and other new information and communication technologies (ICTs) have become an integral part of most Western societies, from the perspective of both individuals and organizations. In this dissertation the evolving role of the Internet and other new ICTs in Finland over the past decade is studied from the perspective of disparity. The ICT disparities are seen to be constructed from two interconnecting elements, access and implications. The main goal of this dissertation is to examine how access, different user purposes, as well as implications, reflect disparities among different socio-demographic and socioeconomic population groups. For the purposes of this work, four research studies, each with its own, specific topic, were constructed. According to the results, age is clearly the most significant element associated with both access and implications for the new ICTs in Finland. Although other examined factors were also significant, they were often associated with individual research topics. In addition, the dissertation will also provide new research elements for future reference.